Մօրուս (Մարգար) Ստեփանի Հասրաթեանի գիտական ելոյթները Բէյրութի Հայկազեան համալսարանում (1965-66) - Պօղոսեան, Վարուժան (տպ. Atlas)
Professor Morus Hasratian (1903-1979), a renowned philologist, archeologist and historian, was a prominent figure in Soviet Armenia. He was the director of the History Museum of Armenia for several years and held high-level administrative positions both in educational and academic institutes. In an unprecedented step in Lebanese Armenian history, professor Hasratian was invited to Haigazian University (College then) as a visiting professor to teach Armenian history, Armenian archeology, and Armenian art history. He taught both at Haigazian and the newly founded AGBU Yervant Husisian Armenological Center. Besides, he gave weekly evening lectures on Armenian history and culture. Dr. Hasratian was the first scholar to be invited to Lebanon for such a long period. It followed the Cold War meltdown and helped in reducing rivalry between the contesting Lebanese Armenian parties.
Keywords: Կենսագրութիւն; Մօրուս Հասրաթեան